The hypocretin/orexin system in sleep disorders: preclinical insights and clinical progress - Chow M (Dove Medical Press, 2016)
Matthew Chow, Michelle CaoDepartment of Psychiatry and Behavioral Sciences, Division of Sleep Medicine, Stanford University School of Medicine, Stanford, CA, USAAbstract: Much of the understanding of the hypocretin/orexin (HCRT/OX) system in sleep–wake regulation came from narcolepsy–cataplexy research. The neuropeptides hypocretin-1 and -2/orexin-A and -B (HCRT-1 and -2/OX-A and -B, respectively), as we know, are intimately involved in the regulation wakefulness. The HCRT/OX system regulates sleep–wake control through complex interactions between monoaminergic/cholinergic (wake-promoting) and gamma-aminobutyric acid-ergic (sleep-promoting) neuronal systems. Deficiency of HCRT/OX results in loss of sleep–wake control or stability with consequent unstable transitions between wakefulness to nonrapid eye movement and rapid eye movement sleep. This manifests clinically as abnormal daytime sleepiness with sleep attacks and cataplexy. Research on the development of HCRT/OX agonists and antagonists for the treatment of sleep disorders has dramatically increased with the US Food and Drug Administration approval of the first-in-class dual HCRT/OX receptor antagonist for the treatment of insomnia. This review focuses on the origin, mechanisms of HCRT/OX receptors, clinical progress, and applications for the treatment of sleep disorders.Keywords: hypocretin, orexin, narcolepsy, insomnia, orexin antagonist, orexin agonist